2019
DOI: 10.3390/su11236574
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis between International Research Hotspots and National-Level Policy Keywords on Artificial Intelligence in China from 2009 to 2018

Abstract: In the last decade, artificial intelligence (AI) has undergone many important developments in China and has risen to the level of national strategy, which is closely related to the areas of research and policy promotion. The interactive relationship between the hotspots of China's international AI research and its national-level policy keywords is the basis for further clarification and reference in academics and political circles. There has been very little research on the interaction between academic researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 77 publications
0
17
0
1
Order By: Relevance
“…Bununla beraber televizyonlarda yayınlanan farklı eğitim seviyeleri için dersleri içeren Çin Eğitim Ağı Televizyonu (http:// www.centv.cn/) da teknik altyapı açısından güçlendiril-miştir. 2018 yılında eğitim ve yapay zeka konulu toplantı ve konferanslara da ev sahipliği yapmış olan Çin'de (Allen G. C., 2019;Gao, Huang, & Zhang, 2019), önemli bir kısmı yapay zeka teknolojisi ile desteklenmiş 22 çevrimiçi eğitim platformu, ilk ve orta okullara ücretsiz çevrimiçi kurslar sağlamak için devreye alınmış; 24.000'den fazla çevrimiçi ders üniversite öğrencilerinin erişimine açılmıştır. Çin Eğitim Bakanlığı, dijital K12 müfredatı sunan ve Çin'in en büyük yedi eğitim teknolojisi şirketi ile işbirliği içinde oluşturulmuş Empower Learning adlı platformu ve son sekiz yılda kaydedilen en iyi öğretmenlerinin derslerinin videolarını, öğretim planlarını ve topluluklarını barındıran kendi kurduğu Educloud adlı platformu öncelikli olarak desteklemiştir (Ning & Corcoran, 2020).…”
Section: çInunclassified
“…Bununla beraber televizyonlarda yayınlanan farklı eğitim seviyeleri için dersleri içeren Çin Eğitim Ağı Televizyonu (http:// www.centv.cn/) da teknik altyapı açısından güçlendiril-miştir. 2018 yılında eğitim ve yapay zeka konulu toplantı ve konferanslara da ev sahipliği yapmış olan Çin'de (Allen G. C., 2019;Gao, Huang, & Zhang, 2019), önemli bir kısmı yapay zeka teknolojisi ile desteklenmiş 22 çevrimiçi eğitim platformu, ilk ve orta okullara ücretsiz çevrimiçi kurslar sağlamak için devreye alınmış; 24.000'den fazla çevrimiçi ders üniversite öğrencilerinin erişimine açılmıştır. Çin Eğitim Bakanlığı, dijital K12 müfredatı sunan ve Çin'in en büyük yedi eğitim teknolojisi şirketi ile işbirliği içinde oluşturulmuş Empower Learning adlı platformu ve son sekiz yılda kaydedilen en iyi öğretmenlerinin derslerinin videolarını, öğretim planlarını ve topluluklarını barındıran kendi kurduğu Educloud adlı platformu öncelikli olarak desteklemiştir (Ning & Corcoran, 2020).…”
Section: çInunclassified
“…The fast development of AI needs to be supported by the necessary regulatory insight and oversight for AI-based technologies to enable sustainable development. Failure to do so could result in gaps in transparency, safety, and ethical standards It shows the constraints of the current AI systems for sustainable development research and emphasises the importance of best practices in this area Vinuesa et al ( 2020 ) 18 Assessing the potentials of digitalisation as a tool for climate change adaptation and sustainable development in urban areas It reveals the capabilities of digitalisation in supporting more effective early warning and emergency response systems, enhancing food and water security, improving power infrastructure performance, enabling citizen engagement Capabilities of digitalisation in supporting more effective early warning and emergency response systems Balogun et al ( 2020 ) 19 Translation of Earth observation data into sustainable development indicators: an analytical framework The study found that the current preferable way for agriculture development lies on smart and precision farming based on the use of digital technologies, which contributes for the reduction of farming costs and the improvement of agricultural profitability It examines the digitalisation process in Russia Boev et al ( 2020 ) 20 Governing AI to benefit SDGs It points out that Big Tech's unregulated rollout of experimental AI poses risks to the achievement of SDGs, with particular vulnerability for developing countries It highlights the risks of unregulated AI causing harm to human interests, where a public and regulatory backlash may result in over regulation that could damage the otherwise beneficial development of AI Truby ( 2020 ) 21 Comparative analysis between international research hotspots and national-level policy keywords on AI in China from 2009 to 2018 It reveals the development of AI in China and the interaction between academics and policy makers in the past ten years, which is of great significance for the sustainable development and effective governance of China’s artificial intelligence AI in China Gao et al ( 2019 ) 22 Translation of Earth observation (EO) data into sustainable development indicators: an analytical framework It demonstrates that although the applicability of EO derived data varies between the SDGs’ indicators, ...…”
Section: Resultsmentioning
confidence: 99%
“…The case studies that address the SD challenges in a broad sense aim to understand and show the role of AI modelling and digitalisation impacts on several domains of SD research (Baumgartner, 2011 ; Khakurel et al, 2018 ; Sebestyén et al, 2020 ; Truby, 2020 ), either by integrating biophysical processes and human dynamics (Steffen et al, 2020 ) or by considering SD from a systemic perspective (Gue et al, 2020 ; Sætra, 2021 ; Vinuesa et al, 2020 ). These case studies use AI algorithms, forecasting models and earth observation data (Andries et al, 2019 ) to support decision-making or policy-making processes for effective governance, helping actors work together to achieve SD (Gao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, papers that acknowledge NNSF and FRFCU funding are cited, on average and in our three-year time window, at higher rates than for publications supported by the European Union and sponsors in Canada, South Korea, Japan and Brazil. Additionally, for 2009. 2020* = 24 May 2020.…”
Section: Research Sponsors Of Artificial Intelligencementioning
confidence: 99%